Full-color-emitting (CuInS2)ZnS-alloyed core/shell quantum dots with trimethoxysilyl end-capped ligands soluble in an ionic liquid. Issue 44 (15th August 2019) - Wang, Huiqing; Hu, Jiayuan; Zhu, Min; Li, Yucheng; Qian, Hao; Shen, Xiaofei; Liebner, Falk; Rosenau, Thomas
Abstract : ZCIS QDs were fabricated by varying ratio stock A to stock B. PL intensity enhanced and blue shift as shell layers increase. Emissions covering 800 nm to 518 nm tuned by compositions or shell layers. Ligand exchanged by MPtMS enable solubility in IL. Abstract : Zinc-copper-indium sulfide (ZCIS)-alloyed quantum dots are emerging as a new family of low toxic I–III–VI semiconductors due to their broad and color-tunable emissions as well as large Stokes shifts. Here, we fabricated a series of ZCIS QDs with tunable PL wavelengths and band-gap energies via a facile strategy by varying the ratio of A1–3 stock (Cu + /In 3+ ) to the B stock (Zn 2+ ) content. The ZnS shell was formed to improve the PL emission efficiency of the core nanoparticles and the PL emission wavelength of the resulting ZCIS/ZnS NCs gradually blue-shifted with an increase in the number of shell layers, resulting in a wide range of emissions from 800 nm to 518 nm that can be tuned by the core compositions or shell layer numbers for ZCIS/ZnS. Finally, the long-chain ligands dodecanethiol/octadecylamine on the quantum dots' surface were efficiently replaced by (3-mercaptopropyl)trimethoxysilane, thus enabling their solubility in an ionic liquid, which was confirmed via GC-MS. It also benefited for the co-dissolution of the polymers and chemical binding with other materials through the reactive silanol group, which provide stable and well-distributed ZCIS/ZnS QDs composites or surface coating by the QDs.